2020
DOI: 10.1002/sctm.20-0223
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit neurospheres as a novel in vitro tool for studying neurodevelopmental effects induced by intrauterine growth restriction

Abstract: The aim of this study was to develop a rabbit neurosphere culture to characterize differences in basic processes of neurogenesis induced by intrauterine growth restriction (IUGR). A novel in vitro neurosphere culture has been established using fresh or frozen neural progenitor cells from newborn (PND0) rabbit brains. After surgical IUGR induction in pregnant rabbits and cesarean section 5 days later, neural progenitor cells from both control and IUGR groups were isolated and directly cultured or frozen at −80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 59 publications
(162 reference statements)
7
23
0
Order By: Relevance
“…This result goes in line with previous evidences in which positive correlation between O4-OL in the CC and birth weight were also found on postnatal day 7 in a moderate IUGR rat model [28]. Going in the same line, a recent article from our group has demonstrated impairments in the O4-OL differentiation after 5 days of incubation in a novel neurosphere culture obtained from our animal model [42]. Disruption in the oligodendrocyte maturation process dur-DOI: 10.1159/000512948 ing neurodevelopment is of relevance as it has been linked with neurodevelopmental impairments later on [15,20,29,38,72].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result goes in line with previous evidences in which positive correlation between O4-OL in the CC and birth weight were also found on postnatal day 7 in a moderate IUGR rat model [28]. Going in the same line, a recent article from our group has demonstrated impairments in the O4-OL differentiation after 5 days of incubation in a novel neurosphere culture obtained from our animal model [42]. Disruption in the oligodendrocyte maturation process dur-DOI: 10.1159/000512948 ing neurodevelopment is of relevance as it has been linked with neurodevelopmental impairments later on [15,20,29,38,72].…”
Section: Discussionsupporting
confidence: 92%
“…In comparison to in vivo studies, the in vitro experimental setting is even more controlled allowing to obtain significant differences even with a smaller number of animals. In fact, a recent study from our group working on the same IUGR rabbit model but performing histological analyses in in vitro conditions has demonstrated impairments in the O4-OL using 4 animals from each group [42]. Another limitation of our study is that we did not explore if the results reported here could be extrapolated to other brain regions and in different time points.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…At 25 days of gestation, a total of 19 pregnant rabbits were subjected to the IUGR induction protocol. The selection of the sample size was made taking into account the mortality related to the IUGR model following previous experience in the group 7,14,29,60 . This sample size would allow us to include the required number of animals for each analysis of the study following previous evidence (see each paragraph for detailed information).…”
Section: Iugr Induction Experimental Groups and Therapy Administrationmentioning
confidence: 99%